Pengaruh Pengawasan dan Pelatihan Terhadap Kinerja Karyawan pada Garuda Plaza Hotel - Denny, A; Prana, Riandani Rezki (CIVITAS: Jurnal Studi Manajemen, 2021)
The purpose of this study was to determine whether there was an effect of supervision and training on the performance of employees at Garuda Plaza Hotel either partially or simultaneously. The study population was 220 permanent employees of Garuda Plaza Hotel. This study uses quantitative methods by distributing online questionnaires to 33 hotel employees to test the validity and reliability of the 68 main respondents who come from Garuda Plaza Hotel employees. The results of the study rejected the three proposed hypotheses, so that it was concluded that supervision and training, either partially or simultaneously, had no effect on performance. Therefore, the authors suggest that a reward and punishment system is programmed as a form of supervision, in addition to making careful planning for a sustainable training program at the Garuda Plaza Hotel.